Risk factors for hypocalcemia after total thyroidectomy - Ariel Shuchleib-Cung; Jose Antonio Garcia-Gordillo; Aldo Ferreira-Hermosillo; Moises Mercado (Cirugía y Cirujanos, 2022)
Background: Hypocalcemia is a common complication of total thyroidectomy; transient hypocalcemia has been reported in up to 68% of the patients. Materials and methods: Chart review of all patients undergoing total thyroidectomy from 2016 to 2020. Clinical, biochemical, and pathological information was registered. We sought correlations between the different variables and the occurrence of post-operative hypocalcemia. This is a retrospective study carried out at a tertiary care teaching hospital. Objectives: The aim of the study was to ascertain the incidence of hypocalcemia after thyroidectomy and to establish potential clinical and pathological risk factors for its development. Results: Three hundred and thirty-seven patients were included in this study (78% female), with a median age of 47 years. The majority (75%) harbored thyroid neoplasms. Post-operative hypocalcemia developed in 43 patients (12.7%). On bivariate analysis, the most significant risk factor was an intraoperative injury of the parathyroid glands (OR = 2.49, 95% CI = 1.11-5.59), followed by a surgical time > 2.5 h (OR = 2.0, 95% CI = 1.03-4.19), concomitant lymph node dissection (OR = 2.45, 95% CI = 1.2-4.9), and placement of drains (OR = 2.40, 95% CI = 1.19-4.87). Only parathyroid injury remained statistically significant on multivariable analysis. Conclusions: The most significant risk factor for the development of post-operative hypocalcemia after thyroidectomy is injury of the parathyroid glands, which is usually noticed by the surgeon.